Analisis Kemampuan Menyimak Cerita Rakyat Melalui Media Audiovisual pada Mahasiswa PBI Universitas Siliwangi - Cici Parida; Nadila Wijayanti Putri; Sopa Namira (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study aims to analyze the listening skills of students of the Indonesian Language Education (PBI) study program at Siliwangi University in understanding folk tales delivered through audiovisual media which is considered capable of increasing student involvement and understanding in the listening process because it combines visual and audio elements simultaneously. The method used in this study is descriptive qualitative, with data collection techniques through listening tests. The results of the study indicate that the use of audiovisual media significantly helps students understand the content of the story, characters, and cultural values ​​contained in folk tales. In addition, this media also motivates students to be more active and focused in listening activities. This study recommends the use of audiovisual media as an alternative to effective listening learning in language teaching, especially in the context of folk tales.